Protein Content, Total Isoflavone, and Antioxidant Capacity of Modified Tempeh Flour Based on Soybean Germination Time - Syafii, Firdaus; Yani, Ahmad (Hypertension Prevention and Control Research Center, The Polytechnic of Health of Banten, 2024)
Differences in soybean germination stages can affect the nutritional content in it, such as protein and isoflavones. These differences in content also affect the antioxidant activity in it. This study aimed to determine the effect of tempeh flour modification based on the soybeans germination time on their protein content, total isoflavones, and antioxidant capacity, and to determine the potential of modified tempeh flour as a better functional food ingredient for people with diabetes mellitus type 2 (DMT2). The research design used in this study was a completely randomized design (CRD) with treatments based on differences in the germination stages of tempeh soybeans before being used to make tempeh flour, namely P0 (0-hour soybean incubation), P1 (20-hour soybean incubation), P2 (30-hour soybean incubation), P3 (40-hour soybean incubation), and P4 (50-hour soybean incubation), with the parameters measured being protein content, total isoflavones, and antioxidant capacity. The resulting data were then tested using ANOVA at the 5% level and Duncan's test. The results showed that modification of tempeh flour based on the duration of soybean germination affected the increase in protein content, total isoflavones, and antioxidant capacity. Treatment P4 (tempeh with soybeans germination for 50 hours) showed the highest value, namely protein content of 55.12%, total isoflavones of 165.57 mg/100 g flour, and antioxidant capacity of 34.12 mg AEAC (ascorbic acid equivalent antioxidant capacity) per 100 g flour. Thus, modification of tempeh flour with P4 treatment has the potential as an ingredient for functional food products with richer nutrition, making it suitable for consumption by people with DMT2.